PV power conditioning system using a three-phase multilevel pulse width modulation inverter employing cascaded Scott transformers - Fernao Pires, Vitor (2019)
Voltage source inverters (VSIs) are power converters that are considered essential in grid connected photovoltaic (PV) generators. There are several types of topologies for these converters. However, from the point of view of high-quality AC output voltage, multilevel inverters are considered the most adequate. Under this context, this study proposes a new structure for the three-phase DC-AC conversion stage for a grid-connected PV system. It consists of two four-leg two-level voltage source inverters that are connected to two PV generators. These inverters are associated with two Scott transformers. The secondary windings of the transformer are connected in a way that allows a series connection. Due to this, a multilevel operation will be achieved. The performance of the proposed power conditioning system will be verified through simulation and experimental results.